Simultaneous X‐ray diffraction and phase‐contrast imaging for investigating material deformation mechanisms during high‐rate loading. (1st January 2015) - Hudspeth, M.; Sun, T.; Parab, N.; Guo, Z.; Fezzaa, K.; Luo, S.; Chen, W.
<x xml:space="preserve">Abstract</x> Using a high‐speed camera and an intensified charge‐coupled device (ICCD), a simultaneous X‐ray imaging and diffraction technique has been developed for studying dynamic material behaviors during high‐rate tensile loading. A Kolsky tension bar has been used to pull samples at 1000 s−1 and 5000 s−1 strain‐rates for super‐elastic equiatomic NiTi and 1100‐O series aluminium, respectively. By altering the ICCD gating time, temporal resolutions of 100 ps and 3.37 µs have been achieved in capturing the diffraction patterns of interest, thus equating to single‐pulse and 22‐pulse X‐ray exposure. Furthermore, the sample through‐thickness deformation process has been simultaneously imaged via phase‐contrast imaging. It is also shown that adequate signal‐to‐noise ratios are achieved for the detected white‐beam diffraction patterns, thereby allowing sufficient information to perform quantitative data analysis diffraction via in‐house software (WBXRD_GUI). Of current interest is the ability to evaluate crystal d‐spacing, texture evolution and material phase transitions, all of which will be established from experiments performed at the aforementioned elevated strain‐rates.